MATERIAL RESTORASI DIREK KEDOKTERAN GIGI SAAT INI - Bambang Irawan (Faculty of Dentistry, Universitas Indonesia, 2015)
Advances in modern dental materials provide patients and practitioners a number of choices from which to create a pleasing and natural looking restoration. This report outlines important features of many of the most popular direct restoratives, with an emphasis on safety and efficacy of each material. The article aims to help dentists to explain their patients the relative and conservative impact of various materials used in dental restoration. On the basis of current knowledge from laboratory and clinical studies, the alternatives discussed in this report, when properly applied, can provide the patient with a safe and effective treatment in the repair of decayed teeth.